ALGORITHM OF MODELING THE TRAJECTORY OF AN AERIAL OBJECT - A. A. Dyatko; S. M. Kostromitski; P. N. Shumski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The method of coordinates calculation of a flight trajectory of the aircraft, adjusted by the reference points and values of radiuses of circles on which the bend in case of change of a direction of the movement should carry out the aircraft is resulted. It is shown that it’s easier to carry out nessesary calculations in special system of the co-ordinates which position in space is defined by three reference points of a trajectory.